Integrating the Science of Aging and Environmental Health Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Understanding and ensuring healthy aging has become increasingly important as the human life span increases with each decade. The need to better understand the role of environmental exposures in the development of aging-related diseases, such as cardiovascular disease, cancer, and dementia, is now an important driver for research at the intersection of aging and environmental health. With that in mind, on June 9-10, 2020, the Standing Committee on the Use of Emerging Science for Environmental Health Decisions of the National Academies of Sciences, Engineering, and Medicine held a 1.5-day workshop to explore how environmental exposures influence or mediate aging and how aging influences environmentally mediated health outcomes. The workshop brought together a multidisciplinary group of experts who described the current state of knowledge in the field as well as ideas for next steps including research opportunities and needs, enabling technologies and analytical tools, and mechanisms to anticipate and use new data to inform environmental health decisions. This Proceedings of a Workshop in Brief summarizes the invited speakers' presentations and the discussion periods that followed each session.

Reflections on the National Science Foundation's Understanding the Rules of Life Program: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
In 2016, the National Science Foundation (NSF) established a five-year program on Understanding the Rules of Life (URoL) to identify generalizable rules that govern biological systems at micro and macro levels. At the request of NSF, the National Academies of Sciences, Engineering, and Medicine convened a series of workshops to explore the achievements of the URoL program. Presenters and participants discussed integration of multi-disciplinary, systems-level approaches, broader implications for studying highly complex systems, future scientific questions and future societal needs, and the production of generalizable rules that apply to different fields and scales. This publication summarizes the presentation and discussion of the workshop.

Antarctic Science: Why U.S. Leadership and Investments Matter - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
As the coldest, most remote, and most extreme environment on Earth, Antarctica provides a unique vantage point for investigating life adaptations, understanding the health of the global climate, and peering into the depths of the Universe. For example, ecological studies in the Dry McMurdo Valley help explain how life survives in extremes, observations of the West Antarctic Ice Sheet reveal vital information about our changing climate, and the Ice Cube Neutrino Observatory provides insights into supernovae, black holes, and similar phenomenon. Since 1959, the Antarctic Treaty has ensured the continent remains a haven for scientific investigation, offering up an invaluable model of global cooperation with U.S. leadership provided by the U.S. Antarctic Program. This booklet, drawing primarily from reports of the National Academies, captures a multitude of insights gained - and sought - from U.S. research investments in this remarkable place. A continued commitment to science, cooperation, and a shared vision for the future are required to build on this rich history of discovery and answer crucial questions in the decades ahead.

Exploring the Science on Measures of Body Composition, Body Fat Distribution, and Obesity: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The National Academies Roundtable on Obesity Solutions hosted a public workshop series in April and June 2023 that explored the current science on measures of body composition and body fat distribution. Discussions focused on the strengths and limitations, and clinical and anthropological perspectives of body mass index (BMI) as a measure of adiposity and health. Presentations also shed light on the connection between misinformation and bias and stigma, as well as challenged current communication strategies to improve messaging about obesity.

Examining the State of the Science of Mammalian Embryo Model Systems: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Because of the recent advances in embryo modeling techniques, and at the request of the Office of Science Policy in the Office of the Director at the National Institutes of Health, the National Academies of Sciences, Engineering, hosted a 1-day public workshop that would explore the state of the science of mammalian embryo model systems. The workshop, which took place on January 17, 2020, featured a combination of presentations, panels, and general discussions, during which panelists and participants offered a broad range of perspectives. Participants considered whether embryo model systems - especially those that use nonhuman primate cells - can be used to predict the function of systems made with human cells. Presentations provided an overview of the current state of the science of in vitro development of human trophoblast. This publication summarizes the presentation and discussion of the workshop.

Enhancing EPA Science Capability for a Complex Future: Recommendations for Use of Title 42 Special Hiring Authority - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
A scientific workforce with cutting-edge skills is critical for the ability of the U.S. Environmental Protection Agency to carry out its mission to protect human health by identifying environmental hazards, evaluating risks to public health and ecosystems, and formulating effective methods for pollution control and prevention. To aid in the selection and hiring of premier scientists and engineers, in 2006, EPA first sought the ability to directly recruit world-renowned scientists and engineers from academia, private industry, and other government agencies under Title 42, Section 209, of the U.S. Code. Title 42 authorizes federal agencies to appoint highly qualified scientists and engineers outside of standard civil service positions. Congress reauthorizes the EPA Title 42 authority in 5-year increments. To guide decisions about the future of the program, Congress asked the National Academies to review past and current EPA use of Title 42 hiring authority and how the program might be improved. The report finds that EPA has used its limited Title 42 authority effectively since 2006 and that Title 42 authority has enabled the hiring of effective scientific leadership and improved the scientific capability and capacity to support the Agency mission. Furthermore, the report finds that Title 42 can help the agency in addressing future environmental complexities. In continuing to enhance its scientific workforce and maintain a position at the forefront of evolving scientific knowledge, EPA would benefit from Congressional approval for permanent Title 42 authority.

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.

The Science of Science Communication II: Summary of a Colloquium (The National Academies Press, 2014)
Successful scientists must be effective communicators within their professions. Without those skills, they could not write papers and funding proposals, give talks and field questions, or teach classes and mentor students. However, communicating with audiences outside their profession - people who may not share scientists' interests, technical background, cultural assumptions, and modes of expression - presents different challenges and requires additional skills. Communication about science in political or social settings differs from discourse within a scientific discipline. Not only are scientists just one of many stakeholders vying for access to the public agenda, but the political debates surrounding science and its applications may sometimes confront scientists with unfamiliar and uncomfortable discussions involving religious values, partisan interests, and even the trustworthiness of science. The Science of Science Communication II is the summary of a Sackler Colloquium convened in September 2013 At this event, leading social, behavioral, and decision scientists, other scientists, and communication practitioners shared current research that can improve the communication of science to lay audiences. In the Sackler Colloquia tradition, the meeting also allowed social and natural scientists to identify new opportunities to collaborate and advance their own research, while improving public engagement with science. Speakers provided evidence-based guidance on how to listen to others so as to identify their information needs, ways of thinking about the world, and the cultural stereotypes regarding scientists. They delved deeply into the incentive systems that shape what scientists study and how they report their work, the subtle changes in framing that can influence how messages are interpreted, the complex channels that determine how messages flow, and the potential politicization of scientific evidence.

Advancing Open Science Practices: Stakeholder Perspectives on Incentives and Disincentives: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The actual and potential benefits of open science include strengthened rigor and reliability, the ability to address new questions,faster and more inclusive dissemination of knowledge, broader participation in research, effective use of resources, improved performance of research tasks, and open publication for public benefit. As one effort to increase the contributions of open science among many, the Board on Research Data and Information of the National Academies of Sciences, Engineering,and Medicine established the Roundtable on Aligning Incentives for Open Science. On September 20, 2019, the Roundtable organized a public symposium in Washington, DC to consider some of the barriers and challenges to open science, as well as ways to overcome them. Key external stakeholders - including researchers, librarians, learned societies, publishers and infrastructure developers - shared their insights on the current state of the research ecosystem, as well as their visions for how open science can function at scale. This publication highlights the presentations of the event.

Science, Technology, and Health Capabilities Within the Department of State and USAID at an Inflection Point: Proceedings of a Workshop-in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The need for U.S. foreign and development policy to be informed by science, technology, and health has perhaps never been more important. Amidst the COVID-19 pandemic, additional global challenges such as climate change, rapidly emerging technologies, and geopolitical competition underscore the importance of strong integration of science, technology, and health into diplomatic and development missions for American prosperity and security. In September 2020, the National Academies of Sciences, Engineering, and Medicine, held a workshop to identify approaches to strengthen science, technology, and health capabilities at the U.S. Department of State and the U.S. Agency for International Development over the next 5 to 10 years. The workshop featured brief presentations by leading American experts from government agencies, universities, research centers, non-governmental organizations, and the private sector, and several leaders from abroad who are actively integrating science and technology developments in the foreign policies of their countries. This publication is a summary of the presentations and the discussions during the workshop.

The State of Anti-Black Racism in the United States: Reflections and Solutions from the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The mission of the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine at the National Academies of Sciences, Engineering, and Medicine is to advance discussions on the barriers and opportunities encountered by Black students and professionals as they navigate the pathways from K-12 and postsecondary education to careers in science, engineering, and medicine (SEM) and highlight promising practices for increasing the representation, retention, and inclusiveness of Black men and Black women in SEM. This proceedings serves as a summary of the presentations and discussions from a capstone workshop, held virtually on December 6 and 7, 2021, to review how anti-Black racism had permeated across the topics covered by the Roundtable over the previous 2 years.

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. But many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including: implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; higher teaching and advising loads; and fewer speaking invitations, among others. There are consequences from this underrepresentation of women for the nation as well: a labor shortage in many science, engineering, and medical professions that cannot be filled unless institutions and organizations recruit from a broad and diverse talent pool; lost opportunities for innovation and economic gain; and lost talent as a result of discrimination, unconscious bias, and sexual harassment. Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine reviews and synthesizes existing research on policies, practices, programs, and other interventions for improving the recruitment, retention, and sustained advancement into leadership roles of women in these disciplines. This report makes actionable recommendations to leverage change and drive swift, coordinated improvements to the systems of education, research, and employment in order to improve both the representation and leadership of women.

Enhancing U.S. Science and Innovation with Novel Cross-Sector Partnerships: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The Government-University-Industry Research Roundtable (GUIRR) of the National Academies of Sciences, Engineering, and Medicine was founded in 1984 to convene the senior-most representatives from government, universities, and industry to define and explore critical issues related to national and global science and technology issues. On June 28-29, 2022, GUIRR convened a workshop for its membership and invited guests to consider current and proposed cross-sector partnerships that enhance science and technology innovation, national security, and national prosperity, and to explore the motives, responsibilities, concerns, and objectives that bring institutions to the table to pursue and sustain partnerships. This publication highlights the presentation and discussion of the workshop.

Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. New research will expand our understanding of our solar system's origins, how planets form and evolve, under what conditions life can survive, and where to find potentially habitable environments in our solar system and beyond. Origins, Worlds, and Life: A Decadal Strategy for Planetary Science and Astrobiology 2023-2032 highlights key science questions, identifies priority missions, and presents a comprehensive research strategy that includes both planetary defense and human exploration. This report also recommends ways to support the profession as well as the technologies and infrastructure needed to carry out the science.

Report Series: Committee on Biological and Physical Sciences in Space: Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
After several decades since the last human visit, NASA is planning to return to the Moon, this time not only to visit but also to carry out extensive scientific experiments, establish a habitat occupied by astronauts, and learn lessons that will help in preparations for the eventual establishment of a human presence on Mars. The Commercial Lunar Payload Services (CLPS) program, overseen by NASA, will provide transport to the Moon for scientists who want to carry out research on the lunar surface or in orbit around the Moon. Recognizing the need to introduce and explain the CLPS program to researchers, the Committee on Biological and Physical Sciences in Space of the National Academies of Sciences, Engineering, and Medicine held a workshop on March 24-25, 2021 entitled \

Advancing Nutrition and Food Science: 80th Anniversary of the Food and Nutrition Board: Proceedings of a Symposium - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
The Food and Nutrition Board (FNB) of the National Academies of Sciences, Engineering, and Medicine was convened in 1940 in response to a request from the U.S. National Defense Advisory Commission to the National Academy of Sciences for aid in studying problems of nutrition in the United States. Today the FNB is the focal point for activities concerned with food, nutrition, and food safety, and their roles in health maintenance and disease prevention. Now in its 80th year, the FNB has continued its growth and expanded its reach both domestically and internationally, providing visionary leadership across a range of nutrition and food science issues toward the improvement of human health. In honor of its 80 years of service to the nation, the FNB convened a public symposium to review the origin and history, policy influence, and future directions of the FNB. This publication summarizes the presentations of the event.

Quantum Science Concepts in Enhancing Sensing and Imaging Technologies: Applications for Biology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Quantum concepts hold the potential to enable significant advances in sensing and imaging technologies that could be vital to the study of biological systems. The workshop Quantum Science Concepts in Enhancing Sensing and Imaging Technologies: Applications for Biology, held online March 8-10, 2021, was organized to examine the research and development needs to advance biological applications of quantum technology. Hosted by the National Academies of Sciences, Engineering, and Medicine, the event brought together experts working on state-of-the-art, quantum-enabled technologies and scientists who are interested in applying these technologies to biological systems. Through talks, panels, and discussions, the workshop facilitated a better understanding of the current and future biological applications of quantum-enabled technologies in fields such as microbiology, molecular biology, cell biology, plant science, mycology, and many others. This publication summarizes the presentation and discussion of the workshop.

Identifying New Community-Driven Science Themes for NSF's Support of Paleoclimate Research: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Sediments, ice, corals, and trees are just some of the natural storehouses of information that help tell the complicated history of Earth2019s climate. Paleoclimate researchers use these 201cproxies,201d in combination with numerical models, to gain understanding of the magnitudes, rates, and drivers of past climate variability with the goal of informing understanding of current and future change in Earth2019s climate system. The Paleo Perspectives on Climate Change (P2C2) program of the National Science Foundation (NSF) has advanced paleoclimate research through proxy development, data-model comparisons, and synthesis work, and has facilitated interdisciplinary collaboration that has contributed to the growth of the field. This new publication highlights discussions at a June 2021 workshop that focused on identifying potential future paleoclimate research directions to further advance understanding of past climate and better inform the public and decision makers about the expected future.

Leveraging Advances in Modern Science to Revitalize Low-Dose Radiation Research in the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Radiation exposure at low doses (below 100 milligray) or low-dose rates (less than 5 milligray per hour) occurs in a wide range of medical, industrial, military, and commercial settings. The effects of exposure at these levels are not fully understood, but there are long-standing concerns that such exposure could negatively affect human health. Although cancer has been linked to low-dose radiation exposure for decades, there is increasing evidence that low-dose radiation exposure may also be associated with cardiovascular disease, neurological disorders, immune dysfunction, and cataracts. Recent advances in research, new tools, and a coordinated multidisciplinary research program could help fill knowledge gaps about the health impacts of low-dose radiation exposures. This report calls for the development of a U.S. research program to study how low doses of radiation affect cancer, cardiovascular disease, neurological disorders, and other disease risks. Research should also better define the impacts of radiation doses, dose rates, types of radiation, and exposure duration. The report estimates 100 million annually for the next 15 years would be required to conduct epidemiological and biological research, and to establish an infrastructure for research.

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors: Proceedings of a Symposium–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. Many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; and higher teaching and advising load, among others. A 2020 report by the National Academies of Sciences, Engineering, and Medicine (the National Academies), Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors, reviews the current state of knowledge of factors that drive underrepresentation of women in science, technology, engineering, mathematics, and medicine (STEMM) and provides an overview of existing research on policies, practices, programs, and interventions for improving the representation of women in these fields. On March 19, 2020, the National Academies held a virtual symposium to share key messages and findings from the report as well as hear from experts on the range of issues addressed in the study. This publication highlights the presentation and discussion of that event.